Synoptic Revision of Diplazium (Athyriaceae) in Rwanda with description of Diplazium cyamudongoense sp. nov. - Fischer, Eberhard; Lobin, Wolfram (Phytotaxa, 2023)
A synoptic revision of Diplazium in Rwanda is provided. Two species, Diplazium humbertii and D. zanzibaricum had already been recorded for the country. Here we describe D. cyamudongoense sp. nov. that can be readily distinguished by the long and brittle scales at the base of the stipe. A key to the species is provided. The spores of the three studied species are documented and compared.